Woody Allen's short stories in Czech translation - Tomášek, Ondřej (2007)
This B. A. Thesis deals with the analysis of the Czech translations of Woody Allen's short stories. This analysis points out the flaws in the Czech translation and suggests better solutions and examines the role of the translator with an experiment.